2010
DOI: 10.1038/ngeo905
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial biogeochemical feedbacks in the climate system

Abstract: The terrestrial biosphere is a key regulator of atmospheric chemistry and climate. During past periods of climate change, vegetation cover and interactions between the terrestrial biosphere and atmosphere changed within decades. Modern observations show a similar responsiveness of terrestrial biogeochemistry to anthropogenically forced climate change and air pollution. Although interactions between the carbon cycle and climate have been a central focus, other biogeochemical feedbacks could be as important in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
406
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 523 publications
(420 citation statements)
references
References 100 publications
1
406
0
1
Order By: Relevance
“…Fire tracks the climate changes in a predictable way that is consistent with known climatic controls on biomass burning (see also [Arneth et al, 2010;Daniau et al, 2010b;Marlon et al, 2009]). The major component of variability in biomass burning over the past 21 kyr reflects the shift from globally cold/glacial to warm/interglacial conditions.…”
Section: Implications Of the Paleo-record Of Firementioning
confidence: 75%
“…Fire tracks the climate changes in a predictable way that is consistent with known climatic controls on biomass burning (see also [Arneth et al, 2010;Daniau et al, 2010b;Marlon et al, 2009]). The major component of variability in biomass burning over the past 21 kyr reflects the shift from globally cold/glacial to warm/interglacial conditions.…”
Section: Implications Of the Paleo-record Of Firementioning
confidence: 75%
“…Changes in global surface temperature caused by the previously described RFs of LULCC and non-LULCC activities lead to a response in carbon uptake by the terrestrial biosphere and the ocean (Mahowald, 2011;Arneth et al, 2010). Moreover, aerosols affect vegetation by redistributing precipitation and changing the ratio of diffuse to direct radiation incident on the surface.…”
Section: B7 Biogeochemical and Carbon-climate Feedbacksmentioning
confidence: 99%
“…It has been found that the varying CO 2 exchanges between atmosphere and the terrestrial biosphere is the main driver of the observed atmospheric CO 2 cycle, including its seasonal cycle and inter-annual variations (Friend et al, 2007;Arneth et al, 2010). This effect has been linked to changes in temperate, boreal and arctic ecosystem properties and processes such as enhanced photosynthesis, increased heterotrophic respiration, and expansion of woody vegetation (Piao et al, 2008;Barichivich et al, 2013).…”
Section: Introductionmentioning
confidence: 99%